Perilaku Penggunaan Tisu Toilet Terhadap Kejadian Keputihan Pada Remaja - Paryono Paryono; Intan Nugraheni (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Toilet Tissue, whitish, Young Women. Whitish in medical terms is called fluorine albus or leucorrhea is liquid released from the genitals. Whitish disease is a problem in women. Normal whitish discharge translucent color, no odor, does not itch and occur before menstruation and after menstruation, sexual stimulation, when a pregnant woman and a state of stress. Abnormal discharge of fluid that comes out cloudy and thick, stinking, rancid, fishy, itchy, fluid quantity many, yellowish or greenish. Behavioral habits that are not good personal hygiene will cause vaginal discharge. Behaviors that can reduce the whiteness using toilet paper after urinating. To determine differences in the use of toilet paper on the incidence of vaginal discharge in adolescent girls at school Veteran 1 Sukoharjo. The study design used was quasi exsperiment with Time Series Design study design is the design of the study using pretest posttest conducted by direct observation. The sampling technique used purposive sampling with a sample of 41 students who have signs of symptoms of vaginal discharge. Mc Nemar statistical test used to determine the effect on the incidence of vaginal discharge toilet paper. Before the treated (preliminary examination) most respondents experienced pathological vaginal discharge as many as 33 students (80.5%), after being given treatment using toilet paper (final inspection) of respondents who experience vaginal discharge pathology as many as 14 students (34.14%). Results of the study showed statistical tests p: 0.000, which means there is the effect of the use of toilet paper on the incidence of vaginal discharge. There is a distinction mark whitish symptoms before and after using toilet paper.